Leaders in computing changing the digital world - Knuth, Donald Ervin 1938-; Booch, Grady; Torvalds, Linus 1969-; Wozniak, Steve 1950-; Cerf, Vinton G. 1943-; Sparck Jones, Karen 1935-2007; Berners-Lee, Tim; Wales, Jimmy; Shirley, Stephanie (British Informatics Society, 2011)
This collection of interviews provides a fascinating insight into the thoughts and ideas of influential figures from the world of IT and computing, such as Sir Tim Berners-Lee, Donald Knuth, Linus Torvalds, Jimmy Wales and Steve Wozniak. It gives an excellent overview of important developments in this diverse field over recent years.
Includes bibliographical references
Keywords: Computers; Information technology; Internet; Ordinateurs; Technologie de l'information; computers; information technology; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference